A Patient with an Unusual Cause Right Lower Quadrant Pain and Vomiting: Pyelonephritis of an Ectopic Right Kidney Masquerading as Acute Appendicitis - Michele N. Lossius; Carlos E. Araya; Dwayne D. Henry; Richard E. Neiberger (Case Reports in Medicine)
An adolescent female presented with one day of abdominal pain and clinical findings of acute appendicitis. CT scan revealed an ectopic right kidney with changes of acute pyelonephritis. This paper underscores the importance of imaging the right pelvis prior to surgical intervention in suspected cases of acute appendicitis in children.